Assessing the Competitiveness and Trends of Indian Sugar in Global Market: A 1999- 2018 Analysis - Utkarsha Pramod Gaware; P. P. Baviskar; Kalpana Kumari; Patibandla Lakshmipriya (Archives of Current Research International, 2024)
Sugar is one of the most produced and traded commodities in the world. India is the second-largest producer and largest consumer of sugar in the world. Therefore, the study was conducted to assess the position of Indian sugar in the international market. The study was based on Time series data of years 1999-2018. To assess the trend, trend analysis was done and, for appraising the competitiveness, export performance ratio and nominal protection coefficient was computed. The cubic model was found best fit for all the particulars considered in the models. Results revealed that production, import quantity and value of sugar had increasing trend while export quantity, value, unit price of export and import of sugar exhibited fluctuating trend. The trade of Indian sugar was found inconsistent in the decadal analysis but overall had a relative advantage in the international market with an EPR vale of 1.11. The higher NPC value of 1.02 pointed out a matter of concern as the Indian sugar was non-competitive in the international market.